An Efficient Synthesis of Tetrahydrobenzo[b]pyran Derivatives Using Sulfonic Acid Functionalized Silica as an Efficient Catalyst - Ghodsi Mohammadi Ziarani; Alireza Abbasi; Alireza Badiei; Zeinab Aslani (E-Journal of Chemistry)
Tetrahydrobenzo[b]pyran derivatives were efficiently synthesized by the reaction of appropriated aromatic aldehydes, malononitrile and dimedone in the presence of SiO2-Pr-SO3H as a nanoporous and recoverable solid acid catalyst, in good to excellent yields. Single crystal x-ray analysis conclusively confirmed the structure of the 2-amino-3-cyano-7,7-dimethyl-4-(4-methylphenyl)-5-oxo-4H-5,6,7,8-tetrahydro-benzopyran.